2013
DOI: 10.17795/jhealthscope-9885
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Knowledge and Practice Regarding Childhood Diarrhea and Diet in Zahedan, Iran

Abstract: Background: Diarrhea infection has been established as one of the major etiologies and risk factors of malnutrition in children. Objectives: The aim of this study was to assess the maternal knowledge, attitude and practices when treating diarrhea in their children less than 5 years old in the Zahedan, south-east province of Iran. Materials and Methods: This cross-sectional study was conducted in urban health centers in Zahedan. Three hundred mothers who had less than five years old children and had been referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 20 publications
8
19
1
Order By: Relevance
“…Ghasemi et al found that 28.80% of the caregivers had good knowledge of the home management of diarrhoea 31 . Khalili et al however reported a much lower level of knowledge of caregivers (3.7%) compared to the present study 23 . There was also a low level of prac ces in the home management of diarrhoea among respondents in this study, with 122(33.89%) having a good level of prac ce.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Ghasemi et al found that 28.80% of the caregivers had good knowledge of the home management of diarrhoea 31 . Khalili et al however reported a much lower level of knowledge of caregivers (3.7%) compared to the present study 23 . There was also a low level of prac ces in the home management of diarrhoea among respondents in this study, with 122(33.89%) having a good level of prac ce.…”
Section: Discussioncontrasting
confidence: 88%
“…In a similar study in Iran 52.00% of mothers correctly iden fi ed the cause of diarrhoea 23 . However, similar study in Nigeria revealed that 35.00% of mothers were aware of contaminated In addi on to ORT, the WHO recommends Zinc supplementa on for the treatment of diarrhoea 25 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a study conducted in south east province of Iran, Khalili, et al reported 81% and 58% mothers acknowledging unsafe water and unclean hands respectively as causes of diarrhoeal illness. 17 Cabatbat, et al in their study conducted in Philippines reports 77%, 34% and 23% mothers acknowledging unsafe drinking water, failure to wash hands after defecating, and after handling faeces respectively as common reasons for diarrhoeal diseases. 15 Surprisingly, in an Indian study conducted earlier, it had been reported just 15% and 6% mothers knowing that dirty water and dirty environment could cause diarrhoea.…”
Section: Discussionmentioning
confidence: 98%
“…Results of another study specified that knowledge of the most of women (64.3%) concerning diarrhea and nutrition was modest and there were only 3.7% had reasonable information [15]. Another study documented the awareness in mothers regarding features of dehydration, 26% mothers were aware about sunken eye as the only clinical feature and 40% mothers reported unclear signs whereas 35% answered two features including thirst and dry skin and there were 80% Mothers who knew about the preparation of ORS [16].…”
Section: Awareness Of Mothers About Diarrhea; a Cross Sectional Compamentioning
confidence: 99%